Abundance and temporal distribution of mullets caught in Merauke City Coastal Waters - Irkham Kurniawan; Modesta Ranny Maturbongs; Bonny Lantang (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
The purpose of this study was to see the abundance and distribution of mullet during the day and night on the coast of Lampu Satu Beach and Payum Beach. This research was conducted in June-August 2020. Determination of the sampling points at the research location using purposive random sampling method. Data analysis used in this research is Relative Abundance (Kr) and Morisita Spread Index (Id). Catches found during the study were 268, with 3 species of mullet, namely Mugil cepalus, Mugil dussumieri and Rhinomugil corsula. During the day, the total number of catches is 148 while at night it gets as many as 120. The highest proportion value of relative abundance was obtained from the two stations, namely Mugil dussumieri species and the lowest was Rhinomugil corsula. The results of the calculation of the morisita distribution index during the day at both stations obtained a value of 1.008 (group). It is also found that at night the two stations get a value of 1.014, which means that at night it is a group category.